Design/CPN - A Computer Tool for Coloured Petri Nets - Christensen, Søren; Jørgensen, Jens Bæk; Kristensen, Lars Michael (DAIMI Report Series, 1997)
In this paper, we describe the computer tool Design/CPN supporting editing, simulation, and state space analysis of Coloured Petri Nets. So far, approximately 40 man-years have been invested in the development of Design/CPN. It is used world-wide by more than 200 companies and research institutions. For the presentation, we draw from the experiences gained in recent industrial application using Coloured Petri Nets in the design, validation, and verification of communication protocols for audio/video systems.